The Relationship between Structural Features of Lignocellulosic Materials and Ethanol Production Yield - Mohammad Saber Bay; Fatemeh Eslami; Keikhosro Karimi (Designs, 2022)
Lignocellulosic materials are a mixture of natural polymers which can be considered a great alternative source of chemical products and energy. Hence, pinewood, poplar wood, and rice straw, as representatives of different types of lignocelluloses, were subjected to several pretreatment types in order to increase ethanol production yield. All pretreatments increased enzymatic hydrolysis and ethanol yield, specifically pretreatment with phosphoric acid. This pretreatment increased ethanol yields by 304.6% and 273.61% for poplar wood and pinewood, respectively, compared to untreated substrates. In addition, a number of analyses, including a BET test, buffering capacity, crystallinity, accessible surface area, and composition measurement, were conducted on the pretreated substrates to investigate their structural modifications in detail. Accessible surface area, as one of the most important parameters for performance of enzymes and microorganisms in the fermentation process, was examined by the water retention value test. The results of this method (using centrifuge) showed that the maximum accessible surface area was related to the pretreated samples with phosphoric acid so that it increased WRV to 132.19%, 149.41%, and 68.44% for poplar wood, pinewood, and rice straw, respectively, as compared to untreated substrates. On the whole, pretreatments restructured and opened up the tangled structure of lignocelluloses, resulting in a considerable increase in ethanol yields. Moreover, in this study, for the first time, a new correlation was presented for each substrate which indicates the relationship between ethanol yield and structural features of the lignocellulosic substrate.